LA SINGULARIDAD DEL OLPE DE ALHAMA DE MURCIA. CULTOS FÁLICOS Y FECUNDIDAD DE LA TIERRA EN EL VALLE DEL GUADALENTÍN - Baños Serrano, José (Revista Murciana de Antropología, 2005)
The roman olpe of lberical tradition found near to Alhama de Murcia has got a painted decoration which represents a phalic motif rounded by vegetables motives, without any known parallelisms. Its possible magical-religious function gives it a very original symbolism within this kind of potteries.